Contested Trajectories of Political Islam: Post-Islamist Reform and the Strategic Turn to Religious Populism - Himam, Mohammad Muafi (POLITEA, 2025)
Islamism, as a political ideology, has undergone significant conceptual transformation within the modern history of the Muslim world. From an early scripturalist and confrontational project aimed at establishing an Islamic order, many Islamist movements have shifted toward more moderate, participatory, and democratic trajectories, theorized as post-Islamism. Drawing on post-Islamism and populism theory, this article develops a conceptual-transformation framework to trace how political Islam moves from ideological Islamism to post-Islamist reform and, paradoxically, to strategic religious populism. The research asks how this trajectory reshapes the relationship between Islamic ideals, democracy, and pluralism in contemporary Muslim politics. Methodologically, it employs qualitative literature-based research and comparative ideological discourse analysis across several Muslim-majority countries, including Iran, Egypt, Turkey, Tunisia, and Indonesia. The findings suggest that post-Islamism offers a synthesis between Islamic values and democratic principles yet simultaneously opens opportunities for religious populism that instrumentalizes Islamic symbols, simplifies moral boundaries between “ummah” and “elite,” and narrows pluralist space. Conceptually, the article proposes an integrated analytical lens for understanding the intertwined evolution of political Islamic ideology and religious populism in an increasingly complex global democratic landscape.